SEJARAH BERDIRINYA NEGARA REPUBLIK INDONESIA SERIKAT (RIS) SAMPAI KEMBALI KE NEGARA KESATUAN REPUBLIK INDONESIA (NKRI) 1949-1950 - Budiarto, Slamet Kabul; Melay, Ridwan (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract : After the proclamation, the Dutch returned to Indonesia by piggybacking on allied forces. The Netherlands intends to re-colonize Indonesia by means other political. The implementation of the Round Table Conference officially mark the founding of the Republic of Indonesia states (RIS) that on December 27, 1949. The purpose of this study were (1) To know the events behind the founding of the Republic of Indonesia States (RIS) (2) To know the condition of government of the Republic of Indonesia states (RIS) (3) To know the end of the Republic of Indonesia states (RIS) to return to the Unitary State of the Republic of Indonesia (NKRI). In this study using methods of historical research. Results from this study is there are some events and happenings behind the founding of the Republic of Indonesia states (RIS) as the Malino Conference, Linggajati, Renville Agreement, Roem-Royen, Inter-Indonesia Conference and the Round Table Conference. At the time of the founding of the Republic of Indonesia States (RIS) so much chaos and upheaval that resulted in the failure of RIS, such as political uprising conducted by Westerling, Andi Azis, and Soumokil. In the economic sector, Indonesia must bear the burden of paying the debt the Dutch East Indies. In the field of military, TNI and the former Colonial Army troops joined the Armed Forces RIS (APRIS). In the field of culture, Indonesia and the Netherlands agreed to establish cooperation such as the exchange of teaching staff and maintenance along cultural objects. In the social field, Indonesia received and ensure employees of Dutch citizen to remain in Indonesia. People of Indonesia considers that the RIS government failed to run the government, so that arose turmoil in various regions carried out by people who are not satisfied and asked back to the Unitary State. Finally, RIS and RI government talks to discuss the re-establishment of the Unitary State. On August 17, 1950 set back the establishment of the unitary state of the Republic of Indonesia (NKRI) with the constitution Constitution Temporary (Provisional Constitution).Key Words: History, RIS, NKRI